Beyond Free-Variation: Scribal Repertoires in Egypt from the Old Kingdom to the Early Islamic Period - Jennifer Cromwell (University College); Eitan Grossman (Hebrew University, Jerusalem) (Jennifer Cromwell (University College); Eitan Grossman (Hebrew University, Jerusalem), 2009)
‘Beyond Free-Variation’ is devoted to the micro-analysis of Egyptian scribal texts and the variation found therein, be it palaeographic, orthographic, or linguistic. The conference aims to raise questions and identify problems related to variation across boundaries of time and period, including ancient Egyptian, Demotic, Coptic, Greek, Latin, and Arabic. By adopting such a comparative and diachronic approach, our overarching aim is to address the stability, or instability, of scribal conventions over time, across languages, and political/cultural changes.